Discrete element modelling of a rock cone crusher - Li, Huiqi; McDowell, Glenn R.; Lowndes, Ian (Elsevier, 2014)
The feasibility of the discrete element method to model the performance of a cone crusher comminution machine has been explored using the particle replacement method (PRM) to represent the size reduction of rocks experienced within a crusher chamber. In the application of the PRM method, the achievement of a critical octahedral shear stress induced in a particle was used to define the breakage criterion. The breakage criterion and the number and size of the post breakage progeny particles on the predicted failure of the parent particles were determined from the results of an analysis of the experimental data obtained from diametrical compression tests conducted on series of granite ballast particles. The effects of the closed size setting (CSS) and eccentric speed settings on the predicted product size distribution compare favourably with the available data in the literature.